Pembuatan E-Pocket Book Berdasarkan Studi Isolasi Bakteri Endofitik Tumbuhan Laban Penghasil Senyawa Metabolit Sekunder Sebagai Bahan Pengayaan Kimia Bahan Alam - Yuwida Romanda Saktilia; Desi Wulandari (Postgraduate, University of Mataram, 2024)
This R&D research refers to the Borg and Gall model which aims to develop and test the feasibility and effectiveness of an E-Book in the form of an interactive flipbook based on Problem Based Learning. The population in the study consisted of 5 small-scale test subjects from class VB and 20 large-scale test subjects from class VA. Data collection techniques use test and non-test techniques in the form of observation, questionnaires, interviews and document data. Validation results by material and media experts show that the product meets the very valid criteria with percentages of 90.23% and 92.17%. Based on the test results, it is known that the product developed is effective in improving student learning outcomes as shown by the average increase of 53 to 81 and the N-Gain test results obtained a gain value of 0.61 (medium). Based on the results of the questionnaire, the responses distributed were very positive from teachers and students. From these results, it is concluded that the E-Book in the form of an interactive flipbook based on PBL is effective for improving science and science learning outcomes and is suitable for use in the learning of class V students at SDN 2 Banjaran.